PARENTING STYLES RELATED TO BEHAVIOR AUTONOMY ON TEENAGER AT JUNIOR HIGH SCHOOL 26TH, MALANG CITY - Wahidyanti Rahayu Hastutiningtyas; Yanti Rosdiana; Srijatun Srijatun (Nurse and Health: Jurnal Keperawatan, 2020)
Background:  Parenting styles is the parent’s model in parenting. By choosing one of parenting styles will influence the relationship between parent and kid. Especially when they started to grow up and became a teenager (McClure et al., 2004).Objectives: This research aimed to analyze correlation between parenting styles and behavior autonomy of teenager at Junior High School 26th, Malang City.Methods:  This research used cross sectional approach, by observing the relationship between parenting styles and behavior autonomy of teenager at SMP 26 Malang city. The research was located at SMP 26 Malang city, on October 2019. They filled in the research questionnaire. The population of research was the female student grade-XIII at SMPN 26 Malang city. The Parenting Styles questionnaire was modified from the Parenting Style Questionnaire likewise for The Behaviour Autonomy from Behavioral Autonomy Questionnaire with an acceptable level of reliability score (α = 0,8; Cronbach’s alpha ≥ 0.6). The study population was 80 students from grade XIII SMPN 26 Malang. In a total of 77 students recruited using purposive sampling as the study participant. The univariate data is analyzed using distribution frequency analysis, and the chi-square test (sig level α = 0.05; CI = 95%) is used to analyze the correlation between variables. SPSS is used for whole data analysis.Results:  Univariate analysis used an analysis by looking at frequency-distribution. Bivariate analysis knew the relationship of independence variable towards dependence variable with statistical-exam chi-square and the limit was (α=0,05) or confidence Interval (CI)=95% processed by using SPSS program. The result of chi-square was gotten p value = (0,002) < (0,050) so that H1 was received.Conclusion:  Parenting styles related to behavior autonomy of teenager at Junior High School 26th, Malang City. The study results are expected to increases the relationship between parenting styles and behavior autonomy among adolescents. Keywords: Parenting Styles, Behavior Autonomy, Teenager, Junior High School 26th of Malang City.